Harmonising environment and development in South Asia - Wijayadasa, K. H. J.; South Asia Co-operative Environment Programme; United Nations Environment Programme; Norway. Direktoratet for utviklingshjelp; Environmental Management Seminar for South Asia (1996 : Colombo, Sri Lanka) (Colombo : South Asia Co-operative Environment Programme, 1997)
Contributed articles presented at the Environmental Management Seminar for South Asia in collaboration with United Nations Environment Programme, Norwegian Agency for Development Co-operation and Govt. of Sri Lanka at Colombo from 16-27 September, 1996.
Includes bibliographical references.
Keywords: Environmental management -- Asia, South -- Congresses; Sustainable development -- Asia, South -- Congresses